Confirmed occurrence of Scorpaena notata Rafinesque, 1810 )Osteichthyes: Scorpaenidae( in Syrian Marine water (Eastern Mediterranean). - بدران معينة (Latakia University Journal -Biological Sciences Series, 2024)
This paper reports a second occurrence of Scorpaena notata Rafinesque, 1810 in Syrian marine water, based on capture of a specimen, 131 mm in total length, with a total body weight of 43 g. The captured was on 25 November 2023, using bottom material cage, at depth about 25m, above rocky bottom, opposite of Banias city (35° 14¢ N; 35° 58¢ E). The specimen is succinctly described including morphometric measurements (to nearest mm), and meristic counts. The specimen was preserved fish Laboratory, in High Institute of Marine Research , Tishreen University. This record confirms this species still present in the Syrian marine water, but needs more observing and monitoring.